3(3x+3)-9=2(5x-22)+45.

Simple and best practice solution for 3(3x+3)-9=2(5x-22)+45. equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3x+3)-9=2(5x-22)+45. equation:



3(3x+3)-9=2(5x-22)+45.
We move all terms to the left:
3(3x+3)-9-(2(5x-22)+45.)=0
We multiply parentheses
9x-(2(5x-22)+45.)+9-9=0
We calculate terms in parentheses: -(2(5x-22)+45.), so:
2(5x-22)+45.
We add all the numbers together, and all the variables
2(5x-22)+45
We multiply parentheses
10x-44+45
We add all the numbers together, and all the variables
10x+1
Back to the equation:
-(10x+1)
We add all the numbers together, and all the variables
9x-(10x+1)=0
We get rid of parentheses
9x-10x-1=0
We add all the numbers together, and all the variables
-1x-1=0
We move all terms containing x to the left, all other terms to the right
-x=1
x=1/-1
x=-1

See similar equations:

| -u=-6-3u | | 4x×23=34 | | r^2+15=61 | | -9f+8=-10f | | X/4-(x-4)/3=5/3 | | 2/1(3-x)-1=4 | | x^2-8x=-15, | | 2x-11+2x-4=13 | | 15z−5=4z | | 8x+2/7x-3=-7/5 | | 20v=680 | | -0,4x+9=0 | | 12t=36−9t | | 10y+1=2y+4 | | (x+4)(2x-7)=90 | | X/2+x/3=x-9 | | x/8-4=0и-0,4x+9=0 | | -3+1/2x=-2 | | 2q-6=20 | | 5x-18=2x-8 | | 14x^2+31x+15=0* | | 6x+42=70-8x | | -3+1/2w=-2 | | 42-2x=x+36 | | q-1/3=-2/3 | | 8(4x─1)─12x=11(2x─6) | | 9x=2x-1 | | 54-2x=4x+36 | | (8x-16°)+(10x-32°)=180° | | t*8/3=336 | | 1/3(m-5)=3/4 | | 2x-5-4x+6=x |

Equations solver categories